Кухня раздельного питания - Семенова Надежда (Кухня раздельного питания, 1998)
Экземпляры: ф16 (20170914) / Инвентарный номер: 54500 / Цена: 20.00 / Сис.шифр: 53.51 / Авт.знак: С 30 / ГРНТИ: 76 / ББК: 53.51